“Rogue” [DEspR+CD11b+] neutrophil subset correlates with severity in spontaneous intracerebral hemorrhage - Herrera, Victoria L. M.; Takahashi, Courtney E.; Nguyen, Mai Q.; Mosaddeghi, Julie Z.; Denis, Ridiane; Greer, David M.; Ruiz-Opazo, Nelson (Frontiers in Neurology, 2022)
Objective Cumulative clinical, cellular, and molecular evidence reinforces the role of neutrophils in secondary brain injury in spontaneous intracerebral hemorrhage (sICH). However, since generalized neutrophil inhibition is detrimental, identification of targetable “rogue” neutrophil subsets associated with sICH severity is key. Methods In a pilot prospective observational study of consented patients with sICH, we immunotyped whole blood to assess circulating neutrophil markers (~day 3 after ICH symptoms onset): (a) DEspR±CD11b± neutrophils by flow cytometry, (b) DEspR±CD11b± neutrophil extracellular trap (NET)-forming neutrophils by immunofluorescence cytology, and (c) neutrophil-lymphocyte ratio (NLR). Using Spearman rank correlation (r) with Bonferroni correction, we assessed the association of neutrophil markers with same-day clinical and neuroimaging parameters of sICH severity, index ICH score, 90-day modified Rankin Scale (mRS) score, and potential interrelationships. As comparators, we assessed same-day plasma biomarkers elevated in sICH: interleukin-6/IL-6, myeloperoxidase/MPO, soluble-terminal complement complex/sC5b-9, endothelin-1/ET-1, and mitochondrial/nuclear DNA ratio (mt/nDNA ratio). Results We detected strong correlations [r(n = 13) > 0.71, power > 0.8, Bonferroni corrected pB < 0.05] for all three neutrophil markers with 90-day mRS score, differentially for DEspR+CD11b+ neutrophil counts, and NLR with perihematomal edema (PHE) volume and for DEspR+CD11b+ NET-forming neutrophil counts with intraparenchymal hemorrhage (IPH)-volume. Only DEspR+CD11b+ neutrophil counts show a strong correlation with index ICH score, same-day Glasgow Coma Scale (GCS) score, and NLR and NET-forming neutrophil counts. The sum of the ICH score and three neutrophil markers exhibited the highest correlation: [r(n = 13) 0.94, pB = 10−5]. In contrast, plasma biomarkers tested were elevated except for MPO but exhibited no correlations in this pilot study. Conclusion Strong correlation with multiple sICH severity measures, NET formation, and NLR identifies DEspR+CD11b+ neutrophils as a putative “rogue” neutrophil subset in sICH. The even stronger correlation of the sum of three neutrophil markers and the index ICH score with 90-day mRS outcome reinforces early neutrophil-mediated secondary brain injury as a key determinant of outcome in patients with sICH. Altogether, data provide a basis for the formal study of the DEspR+CD11b+ neutrophil subset as a potential actionable biomarker for neutrophil-driven secondary brain injury in sICH. Data also show ex vivo analysis of patients with sICH neutrophils as a translational milestone to refine hypotheses between preclinical and clinical studies.